1998
DOI: 10.1007/bf02467469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additional carbon and boron alloying on the structure and mechanical properties of alloy VT22

Abstract: The creation of high-strength heat-resistant alloys based on titanium is of great scientific interest. Doublephase titanium (at + 13) alloys are widely used at present. The alloying sets for these alloys are mainly developed with the purpose of increasing their strength and heat resistance by solution strengthening of the phases with substitutional elements. However, the increasing strictness of the requirements on the level of their mechanical properties makes it necessary to create titanium alloys that can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In the present study no α" phase appears contrarily to the findings by Shevel'kov [22], because shorter ageing times used were not sufficient to produce large concentration gradients within β phase. The obtained microstructures are in good agreement with the existing literature [13,14,31,32].…”
Section: The Evolution Of Microstructuresupporting
confidence: 90%
See 3 more Smart Citations
“…In the present study no α" phase appears contrarily to the findings by Shevel'kov [22], because shorter ageing times used were not sufficient to produce large concentration gradients within β phase. The obtained microstructures are in good agreement with the existing literature [13,14,31,32].…”
Section: The Evolution Of Microstructuresupporting
confidence: 90%
“…3). The presence of similar white titanium carbide particles in β-Ti alloys is reported in the literature [20,32,34]. In another study [35], the effect of carbon content on structural changes in α phase in Ti-5Al-5Mo-5V-3Cr alloy has been discussed but they do not mention the presence of such particles.…”
Section: The Evolution Of Microstructurementioning
confidence: 86%
See 2 more Smart Citations
“…Boron, unlike other interstitial elements such as oxygen and hydrogen, is almost insoluble in titanium in the solid state and, thus, does not embrittle the lattice. Recent studies suggested that a trace of boron addition to conventional titanium alloys such as Ti-64, Ti-6242s, Beta 21s and Ti-1024 etc., obtained obviously grain refinement in the as-cast structures [6][7][8][9][10][11][12]. The as-cast ingot with fine grains could avoid the breakdown process and reduce the process cost [13].…”
Section: Introductionmentioning
confidence: 98%